Biological fermentation of syngas - Alves, J. I. (2010)
Synthesis gas (or syngas) can be produced from a variety of materials including commonly-used fossil fuels, but also renewable organic compounds such as poorly degradable biomass sources and wastes, through gasification. Syngas is a mixture composed of mainly H2, CO and CO2 that can be used in a biological process for the production of fuels or usable chemicals. The main goal of this work is to explore the potential of biogas or other valuable compounds production from syngas.